Study on Stability Characteristics of Earth Rock Dam Slope under Different Rainfall Conditions Combined with the Variation of Reservoir Water Level - LIANG Yukai (Renmin Zhujiang)
To study the influence of rainfall and the variation of reservoir water level on the stability characteristics of earth rock dam slope,based on the principle of unsaturated seepage,this paper conducts the finite element simulation of dam slope stability under different rainfall intensities,different rainfall types (three in total) and different variation rates of reservoir water level.The results show that:①When there is no rainfall,the variation rate of water level mainly affects the time when the safety factor of upstream and downstream dam slopes tends to be stable,and the variation range of safety factor of downstream dam slope is smaller than that of upstream dam slope.②When the different intensities of rainfall and the variation of reservoir water level occur simultaneously,the influence of rainfall intensity on the safety factor of upstream dam slope is small.The most dangerous condition of upstream dam slope is that the water level falling rate is 4 m/d and the rainfall intensity is 40 mm/d,and the safety factor is 1.298;while that of downstream dam slope is that the water level rising rate is 4 m/d and the rainfall intensity is 40 mm/d,and the safety factor is 1.443.③When different types of rainfall and the variation of reservoir water level occur simultaneously,the analysis of dam slope stability can be divided into three stages,and the safety factor changes with the rainfall type at each stage presents complex characteristics.The study provides a reference for correctly understanding the stability law of earth rock dam slope under different intensities and types of rainfall combined with the variation of reservoir water level.